CFD analysis of aeroponic nutrient spray characteristics for enhanced plant nourishment in sustainable agriculture - Aeswin Lawrance; K. Vishnu Ram; R. Harish (Smart Agricultural Technology)
This paper presents a detailed Computational Fluid Dynamics (CFD) analysis of nutrient spray flow characteristics from an aeroponic nozzle for enhancing plant nourishment in sustainable agriculture systems. The study investigates the flow development, velocity distribution, and multiphase turbulent characteristics of the nutrient spray emitted from the nozzle and its interaction with plant roots. The impact of nozzle diameter on nutrient spray performance is examined. Additionally, critical parameters such as the angular orientation of the nozzle and the Reynolds number are also investigated. The nutrient spray mist emitted from dual nozzles shows significant liquid fraction development as it progresses towards the plant roots. Initially, the mist is emitted uniformly, and as it evolves, the jets merge, increasing in intensity and covering a wider area, thereby enhancing nutrient concentration around the roots. Velocity analysis reveals high initial velocities near the nozzle, with increasing magnitude along the spray path but lower velocities near the roots due to no-slip boundary conditions. The merging jets create a unified stream, generating turbulent flow with multiple vortices that enhance nutrient dispersion throughout the aeroponic system. Findings indicate that reducing nozzle diameter significantly increases both spray velocity and turbulent kinetic energy. A notable increase is observed when the diameter is reduced from 40 mm to 25 mm, resulting in a 69.45% increase in spray velocity and a 58.18% increase in turbulent kinetic energy. Higher angles and Reynolds numbers lead to increased spray velocity and kinetic energy, with the highest values observed at a 55∘ orientation. Specifically, increasing the nozzle angle from 35∘ to 50∘ boosts the spray velocity by 31.42% and the turbulent kinetic energy by 37.51%. This research provides valuable insights into the optimal design of aeroponic nozzles, highlighting the importance of nozzle diameter, angular orientation, and Reynolds number in maximizing nutrient delivery efficiency. The findings contribute to the advancement of sustainable agriculture by improving the design and performance of aeroponic systems for enhanced plant nourishment.